Insights into the Tautomerism in meso‐Substituted Corroles: A Variable‐Temperature 1H, 13C, 15N, and 19F NMR Spectroscopy Study. Issue 6 (22nd January 2014) - Szymański, Sławomir; Paluch, Piotr; Gryko, Daniel T.; Nowak‐Król, Agnieszka; Bocian, Wojciech; Sitkowski, Jerzy; Koszarna, Beata; Śniechowska, Justyna; Potrzebowski, Marek J.; Kozerski, Lech
Abstract Tris(pentafluorophenyl)corrole and its 15N‐enriched isotopomer were studied in [D8]toluene solution by 1D and 2D variable‐temperature NMR techniques to establish the mechanisms of tautomerization of the NH protons inside the interior of the corrole macrocycle. Three such rate processes could be identified of which two modulate the spectral line shapes at temperatures above 205 K and the third is NMR‐inaccessible as it is very fast. The latter involves the proton engaged in an unsymmetrical proton sponge unit formed by two pyrrole nitrogen atoms. Temperature and concentration dependences of the two remaining processes were determined. One of them is purely intramolecular and the other is intermolecular at low temperatures, with growing contribution of an intramolecular mechanism at elevated temperatures. The proposed microscopic mechanisms of all these processes are semi‐quantitatively confirmed by quantum chemical calculations using density functional theory.